Architecture's pretexts : spaces of translation - Kanekar, Aarati (London: Routledge, 2015)
"This book considers ideas from one medium that might have been appropriated and transformed by others; highlighting their uniqueness and limitations. More specifically, this book addresses the manner in which this translation occurs across different forms of creation, construction, and expression. The intention is to address broader questions of representation and construction of meaning across media that eventually impact processes of design formulation. By integrating knowledge and modes of thinking from multiple means of expression, they are able to advance their understanding in ways that would be impossible through a unitary line of inquiry"--
Introduction. On Translation and Spatial Construction of Meaning -- Space of Poetic Allegory. Translating The Divine Comedy : Terragni's Danteum as a Projection of Meaning Across Symbolic Forms -- Space of Narrative Structure. The Shaping of Romeo and Juliet : Eisenman's Moving Arrows Eros and Other Errors -- Space of Sound & Music. Architecture as a Performative Instrument : Zumthor's Soundbox -- Space of Representation. The Generative Maps of Perry Kulper and Smout Allen -- Space of Montage. Movement, Assemblage, and Appropriation in Koolhaas' Kunsthal.
Includes bibliographical references (pages 155-168) and index.
Keywords: Architectural design; Idea (Philosophy) in art; Influence (Literary, artistic, etc.); ARCHITECTURE / Methods & Materials; ART / Criticism & Theory; MUSIC / History & Criticism